The relationship between behavioral factors, weight status and a dietary pattern in primary school aged children: The GRECO study. Issue 1 (February 2019) - Magriplis, Emmanuela; Farajian, Paul; Panagiotakos, Demosthenes B.; Risvas, Grigoris; Zampelas, Antonis
Summary: Background & aims: Numerous factors have been associated with the increase in childhood overweight and obesity, including environmental, dietary and behavioral. The latter have been associated with unhealthy eating behaviors but studies of their relation to dietary patterns are limited. Dietary patterns serve as a better means to evaluate children's diet and risk of obesity and therefore the aim of the study was to examine the relationship of behavioral factors with a specific dietary pattern developed for children (child derived Food Index (cdFI)), and to assess how behavioral and diet are related to children's weight status when addressed together in a model. Methods: Study included school-aged children (n = 4434) from the Greek Childhood Obesity study (GRECO), a cross-sectional survey. Participants self-reported behavioral habits and dietary intake, using a semi-quantitative food-frequency questionnaire (FFQ). A high dietary pattern-cdFI is related to a healthier dietary pattern. Anthropometric data were measured. Multiple linear and logistic regressions were performed, adjusting for age and gender. Results: The dietary pattern was positively associated with sleep, family meals and study hours, and was inversely associated with total screen time, frequency of eating out and eating while on some screen. Overweight and obese children were more likely to have a lower cdFI score (2%), sleep less (8%) and report more study hours (6%). Conclusion: In order to reduce and prevent child overweight and obesity, interventions probably need to address specific behavioral and dietary patterns together.